The New Approach For Zonal Subdivision Of Pliocene - Pleistocene Nannoplankton Biostratigraphy In Waipoga-Waropen Basin, Papua - Panuju Panuju (Testing Center for Oil and Gas LEMIGAS, 2009)
Waipoga-Waropen Basin is placed in northern part of Papua on the island of NewÂ Guinea. The gas discoveries had been made since 1958 in this basin, however, no economic value of reserves lead to the not producing basin state until this time. The main problem in Waipoga-Waropen Basin is great thickness of Pleistocene sedimentary layers (until 7500m) as product of turbidite system (Wold & Barret, 2000). This makes difficulty in well section correlation based on the conventional biostratigraphy since individual layers within that section is being small part of biozone. Many reworked nannoplankton as implication of turbidite deposit are also being complicated aspect in biostratigraphic analysis. The Pleistocene ranges from 1.806 m.a. to 11.550 k.a. It was the most recent episode of global cooling or ice age took place. In nannoplankton biostratigraphy, this age is characterized by the extinction of Discoaster brouweri (Discoaster group) at the bottom and the first occurrence of Emiliania huxleyi at the top. The quatitative nannoplankton investigation of â€œTâ€ well has been done, and there is evident that its sedimentary section gives the excellent nannoplankton assemblages to subdivide Pleistocene age sediments of Waipoga-Waropen Basin (Zone NN19) into 9 subzones. Biomarkers from the bottom to the top consist of: LO of Discoaster brouweri, FO of Gephyrocapsa caribbeanica, FO of Gephyrocapsa oceanica, LO of Cacidiscus macintyre , LO of Helicosphaera sellii, FO of Reticulofenestra asanoi, FO of Gephyrocapsa parallela, LO of Reticulofenestra asanoi, FO of Helicosphaera inversa and LO of Pseudoemiliania lacunosa. The sediments belong to zone NN 20 that placed in the uppermost part of Pleistocene were not analysed.